The effectiveness of using Google educational apps to develop self-efficacy among education technology students - El Koshiry, AMR; Eliwa, Entesar Hamed I; Abd El-Hafeez, Tarek; Tony, Mohamed Abd Allah (Research Journal in Advanced Humanities, 2025)
This study investigates the effectiveness of Google Educational Apps in enhancing self-efficacy among education technology students at Minia University. Utilizing a quasi-experimental design, the research involved 28 graduate students from the Special Diploma in Education Technology, who engaged with an educational website developed on Google Sites. Multiple assessment tools, including performance tests and self-efficacy measures, were employed before and after the intervention to evaluate skill acquisition and changes in self-efficacy levels. Statistical analyses indicated both significant improvement in both self-efficacy and performance scores, with the large effect size indicating substantial gains in learning. Performance test scores improved substantively from pre-test (M = 19.64) to post-test (M = 50.11), and self-efficacy levels also grew substantially (t = 63.69, p < 0.001; η² = 0.993). These results confirm the large-scale positive relationship between usage of Google Educational Apps and improved technological competence and learner confidence. The study highlights the importance of cloud-based applications in meeting the evolving needs of the digital learning environment. It recommends the use of such apps at universities to improve student participation, foster collaborative learning, and prepare future educators for technology-rich classrooms. The results provide real-world implications for enhancing educational quality by strategic technology adoption.